Dynamics of Adoption of Recommended Rice Production Technologies among Migrant Farmers - N. Sai Krishna; Shaik N. Meera; P. Muthuraman (Journal of Agricultural Extension Management, 2025)
Migration is a complex social process and is symptomatic of basic economic and social change. Ever since the inception of the green revolution and irrigation development in certain areas, rural to rural migration has increased particularly during the last four decades. The increased inflow of migrant farmers has far reaching socioeconomic implications, as well as the overall agricultural development of the region, which warrant scientific investigation. It is recorded that in India, rural to rural migration is 59.30 per cent whereas rural to urban, urban to urban and urban to rural migration are 21.20, 12.95 and 6.25 per cent, respectively. In Karnataka it is 55 .00, 20.50, 32.50 and 8.20 per cent, respectively. Among intra-district, inter-district and inter-state migration in both India and Karnataka, intra-district migration is leading with 63.5 and 57.95 per cent, respectively (Patil, 1991). The push factors such as floods, droughts, natural calamities, poverty and indebtedness (economic factors), and strained relations (social factors) also cause migration (Gupta and Bhakoo, 1980; Gupta, 1991 and Kishore kumar and Bijimolbaby, 1997)